Sources of psychological stress and methods of confronting it among students of the University of Hail in the Kingdom of Saudi Arabia - Suliman, Mohamed Mohamed Alhadi; Elsir, Ahmed Suliman; Al-Sayed, Othman Fadl (Journal of Educational and Psychological Sciences, 2021)
The study aimed to investigate the relationship between the style of sources of psychological stresses and methods of confronting it of Hail university students. The researchers designed a scale to investigate sources of psychological stresses and methods of confronting it. The researchers applied the tools on a sample of 400 (males and females) of Hail university students. The collected data analyzed statistically by SPSS. The results showed the sources of stress are high among Hail University students. Hail University students are characterized by high coping methods to stress. The sources of psychological stresses and methods of coping are conversely correlated.